Wage compression and employment in Europe : first evidence from the structure of earnings survey 2002 - Mourre, Gilles; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
This paper aims at examining wage compression in Europe using the publicly available data on wages drawn from the Structure of Earnings Survey 2002. By wage compression, it is meant here that the difference in productivity across workers or firms is only partly reflected by the difference in wages. The paper specifically considers the existence of wage compression both across occupations and levels of education by means of cross-sectional econometric analysis. • Looking at wage compression across occupations, robust evidence gives some support to the conventional view that there is a compressed wage distribution in Europe. • Wage compression mainly occurs in continental and southern countries, whilst no compression is detected in Anglo-Saxon countries and mixed evidence is found in Northern European countries.
Economic Papers